Simulated transport time and distance from nuclear power plant to nearest university hospital in Korea - Kim, Hyo Joong; Kim, Yong Han (International Journal Of Community Medicine And Public Health, 2017)
Background: Nuclear accident has a possibility of many injured people and requires urgent transfer to hospital. We investigated simulated transport time and distance from nuclear power plant to nearest university hospital by motor vehicle in Korea. Methods: This study was based on scenario design. Transport time and distance was measured on internet mapping service. We decided less than one hour is optimal on estimated arrival by motor vehicle. Results: Four nuclear power plants and twenty four nuclear reactors are operating in Korea. Each estimated arrival time to nearest university hospital is 37 min, 47 min, 1 hour 32 min and 2 hours 37 min, respectively (Gori, Wolsung, Yeonggwang and Uljin). Measured distance is 25, 27, 69 and 157 kilometers, respectively. Conclusions: Gori and Wolsung nuclear power plants require other hospital in close location or more rapid transport system.